Computed tomographic coronary angiography: how many slices do you need?. Issue 5 (13th April 2006) - Peebles, C
Abstract : While increasing the number of slices in multislice computed tomography clearly brings benefits in terms of detecting significant coronary disease, heavy calcification remains a problem, as does the high radiation burden